Situation Report: Romania, 11 August 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Turkey's Prime Minister Visits Romania The New Five-Year Plan Romania Continues to Renounce Reform The Plight of Romanian Children / by Crisula Stefanescu Patriarch Justin Moisescu Dies / by Dan Ionescu The 1941 Iasi Pogrom Is Commemorated / by Anneli Maier